PROBLEMS OF SYSTEMIC ARTERIAL HYPERTENSION IN RHEUMATOLOGICAL DISEASES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Cardiovascular complications, caused by the development of arterial hypertension and early atherosclerotic damage to blood vessels, are the leading cause of death in rheumatic diseases (RD). The results of the conducted studies convincingly demonstrate the role of the inflammatory process in the occurrence and progression of hypertension in RD. In RD with arterial hypertension, there was hyperactivation of the sympathoadrenal system with an increase in the level of vasoactive amines (adrenaline and noradrenaline) and an increase in the plasma renin level. In RD, the indicators of daily blood pressure monitoring clearly correlated with kidney damage and the activity of the inflammatory process.